Residential satisfaction indicator: Latin American evidence - Zea-De la Torre, Michelle-Ángela; Jimber-Del Río, Juan-Antonio; Nuñez-Tabales, Julia; Rey-Carmona, Francisco-José; Vergara-Romero, Arnaldo (International Journal of Strategic Property Management, 2025)
Latin American construction companies, particularly in Ecuador, operate in a highly competitive environment. In this context, achieving customer satisfaction is a primary objective for the success of real estate projects. This research aims to develop a comprehensive residential satisfaction index that includes sustainability dimensions, based on global satisfaction indices and structural equation modeling. This study will enable residential builders to assess their performance from the customer’s perspective and make strategic decisions aimed at improving quality, which, in turn, will lead to greater customer satisfaction in future projects. The findings of this research will provide valuable input for decision-making in the real estate sector, with a focus on the Latin American context.